Spiritual Emotional Freedom Technique (SEFT) terhadap Kualitas Hidup Pasien HIV/AIDS - Defia Roza; Sila Dewi Anggreni; Heppi Sasmita; Yessi Fadriyanti; Nova Yanti (Jurnal Keperawatan Silampari, 2020)
This study aimed to determine the effectiveness of SEFT interventions in improving the quality of life of HIV / AIDS patients in Padang City. The design of this study was a Quasi-experimental design with one group pretest and posttest. This study found that the average quality of life of HIV patients before SEFT administration was 97.07, and the average rate of life of HIV patients after SEFT administration was 102.6. It can be seen that the mean difference between before and after SEFT action is 5.57 with a standard deviation of 6.98. The statistical test results obtained p-value = 0.011. In conclusion, there is a significant difference between the quality of life of HIV patients before and after SEFT treatment. Keywords: HIV, Quality of Life, SEFT